Environmental, Social and Governance Disclosure Associated with The Firm Value. Evidence from Energy Industry - Daniela Constantinescu; Chirata Caraiani; Camelia I. Lungu; Pompei Mititean (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - Is there an association between ESG factors disclosure and the firm's value for the companies acting in energy sector? Motivation - Identifying whether a connection exists between the ESG factors disclosure and firm's value is a current and much debated matter, with a focus on the presentation of non-financial information. The necessity of demonstrating the existence of an association is based on the inclusion of non-financial information in the company's corporate reporting combined with financial information. Non-financial information presents the long-term prospects of a company and is focused on the value creation process, as opposed to financial information which is limited to historical data and short-term goals such as profit maximisation. In order to describe the value creation process, the company is analysed from different stakeholders' points of view (customers, suppliers, employees, local community, government, environments activists, etc.) and the interdependencies created between the company and these stakeholders. Therefore, by choosing to present a more holistic view of a company, the management of the company may attract new capital from investors by showing that there is a positive association between ESG factors and firms' value (Sadiq et al., 2020; Wong et al., 2020). Idea - This paper assesses the possibility of an association between ESG factors and firm's value by developing two linear regression models. Data - The data used for the research was collected from Thomson Reuters platform based on Top 100 Global Energy Leaders established by the analysists from Thomson Reuters. Tools - The SPSS statistic program was used to apply the two research models on the data collected. Findings - The main findings of the research is that there is an association between ESG factors disclosure and firm's value, and based on the type of the connection (positive or negative), companies may include aspects regarding non-financial information, namely ESG factors, which could attract new capital. Contribution - This paper contributes to the previous research conducted on the disclosure of ESG factors and its influence on firm's value by showing that there is an association between ESG factors disclosure and the value of the company. The evidence obtained based on the two research models applied to the dataset may persuade the management of the companies to include non-financial information in their corporate reporting.
Keywords: M14; 650; Environmental; social; and corporate governance (ESG); firm's value; corporate performance; Energy industry